1964
DOI: 10.1126/science.143.3612.1328
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Synthesis in the Pineal Gland: Effect of Light Mediated by the Sympathetic Nervous System

Abstract: Exposure to light reduces the ability of the rat pineal gland to synthesize melatonin and decreases the weight of the gland. When the sympathetic nerves to the pineal gland are cut, light no longer has an effect on melatonin synthesis or pineal weight. The response of the gland does not require that the gonads or the pituitary gland be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
2

Year Published

1965
1965
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(57 citation statements)
references
References 10 publications
0
55
0
2
Order By: Relevance
“…In addition to its potent bleaching action on frog skin melanophores (Lerner et al, 1958), melatonin has been found to have an inhibitory effect on the response of the thyroid to methylthiouracil (Baschieri, De Luca, Cramarossa, De Martino, Olivario & Negri, 1963), on the development of rat seminal vesicles (Kappers, 1962) and, when given in minute doses for long periods, on ovarian growth and oestrus (Wurtman, Axelrod & Chu, 1963). The sensitivity to light of the size (Wurtman, Roth, Altschule & Wurtman, 1961;Fiske, Pound & Putman, 1962), histological structure (Roth, Wurtman & Altschule, 1962) and chemistry (Quay, 1961(Quay, , 1963Quay & Halevy, 1962) of the pineal gland has been related to melatonin synthesis by the finding (Wurtman, Axelrod & Fischer, 1964;Wurtman, Axelrod & Potter, 1964) that pineal hydroxyindole-o-methyl transferase activity is also markedly influenced by exposure to light.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its potent bleaching action on frog skin melanophores (Lerner et al, 1958), melatonin has been found to have an inhibitory effect on the response of the thyroid to methylthiouracil (Baschieri, De Luca, Cramarossa, De Martino, Olivario & Negri, 1963), on the development of rat seminal vesicles (Kappers, 1962) and, when given in minute doses for long periods, on ovarian growth and oestrus (Wurtman, Axelrod & Chu, 1963). The sensitivity to light of the size (Wurtman, Roth, Altschule & Wurtman, 1961;Fiske, Pound & Putman, 1962), histological structure (Roth, Wurtman & Altschule, 1962) and chemistry (Quay, 1961(Quay, , 1963Quay & Halevy, 1962) of the pineal gland has been related to melatonin synthesis by the finding (Wurtman, Axelrod & Fischer, 1964;Wurtman, Axelrod & Potter, 1964) that pineal hydroxyindole-o-methyl transferase activity is also markedly influenced by exposure to light.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin production and release are, in all species examined, greatest during the daily dark period, falling precipitously with the onset of the light period. Normally this circadian rhythm is synchronized by nerve impulses generated by light acting on the retinas and transmitted to the pineal via norepinephrine released from its sympathetic nerves (15 The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advtisement" in accordance with 18 U. S. C. §1734 solely to indicate this fact.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to photic influence on the secretory activity in the pineal body (WURTMAN et al, 1964), its endocrine effects on the central nervous system have been proposed (ANTON-TAY and WURTMAN, 1969;NIR, BEHROZI, AssAEL et al, 1969;QUAY, 1965QUAY, , 1970. In fishes, there exists a reciprocal BARTHELD and MOLL, 1954;KAPPERS, 1960;SMITH, 1971).…”
Section: Pineal Bodymentioning
confidence: 99%